The Effect of Some Non-Genetic Factors on Milk Production and Offspring Growth in the Iraqi Local Goat Breed - Tuama, Bashar Fadhil (American Journal of Biology and Natural Sciences, 2025)
This work sought to investigate how several non-genetic elements affected goat milk production and offspring growth performance. The findings showed that neither daily nor total milk yield (P > 0.05) was significantly affected by the sex of the offspring. By contrast, the type of birth had a very significant impact (P < 0.01), with twin-bearing does outperforming those with single births in milk production. Maternal age also showed a very significant effect (P < 0.01), since older does produce more milk, With regard to mother weight, heavier does shows noticeably higher milk yield (P < 0.05). Milk output was not much affected by month of birth (P > 0.05), implying constant environmental and management conditions all year long. But the production year had a very significant impact (P < 0.01); 2024 had better milk yield than all other years). Regarding growth performance, the sex of the offspring had no appreciable impact on birth weight (P > 0.05), but had a highly significant effect on weaning weight and daily weight gain (P < 0.01), with male children outperforming female ones most likely due to androgenic influence. The type of birth also had a highly significant effect (P < 0.01) on all growth parameters since single-born children showed better performance than twins, probably due to more favorable intrauterine and postnatal conditions. Birth or weaning weights (P > 0.05) were not much influenced by maternal age; but, daily weight gain (P < 0.05) was much influenced by it. With heavier does producing better-performing children, maternal weight showed a highly significant effect on birth weight and daily weight gain (P < 0.01) and a significant effect on weaning weight Growth characteristics showed no appreciable influence from month of birth (P > 0.05). Similarly, the production year had a highly significant impact (P < 0.01) on daily weight gain in 2024, birth or weaning weights did not significantly change (P > 0.05).